Phenology and content of capsaicinoids in chili fruits produced under greenhouse conditions - Morales Fernández, Sigfrido David; Moreno Velázquez, Delia; Trinidad de Jesús, Salvador; Vázquez Cruz, Fabiel; Ibáñez Martínez, Armando; Tobar Reyes, J. Refugio (Revista Mexicana de Ciencias Agrícolas, 2020)
In the present investigation, the development and yield of 10 chili genotypes were evaluated under greenhouse conditions and in the laboratory the content of capsaicinoids in fruits with different stages of maturity was determined, coming from seven municipalities in the state of Puebla. The work was carried out at the Faculty of Agrohydraulic Engineering of the Benemerita Autonomous University of Puebla, San Juan Acateno, Teziutlan, Puebla. The experimental design used was complete random blocks with four repetitions. Phenology variables were recorded and the content of capsaicin and dihydrocapsaicin was determined by high performance liquid chromatography (HPLC). The Cera Amarillo chili had the highest growth cycle (4 360 degrees day, p≤ 0.05) among all genotypes, while Cera Rojo registered the maximum weight of the fruit (795 g, p≤ 0.05), attributed to its greater diameter and average weight. The highest content of capsaicin, dihydrocapsaicin and total capsaicinoids (2.65, 0.49 and 2.99 mg g-1, respectively) was presented in the state of commercial maturity of the fruits. The Mirasol chilli showed greater stability in the content of capsaicin, dihydrocapsaicin and total capsaicinoids when changing from the state of physiological maturity to commercial.